Does Spiritual Well-Being Affect Death Anxiety and Psychological Resilience in Cancer Patients? - Turan, Gulcan B.; Dural, Gul (Sage Publications Inc, 2025)
This study was conducted to research the effects of spiritual well-being on death anxiety and psychological resilience in cancer patients. This cross-sectional, descriptive and correlational study was carried out with 260 cancer patients who were admitted to oncology and haematology outpatient clinic of a university hospital in east of Turkey between October 2021 and April 2022. The data were collected by using Personal Information Form, Spiritual Well-being Scale (FACIT-sp), Death Anxiety Scale (DAS) and The Brief Resilience Scale (BRS). It was found that mean DAS total score of cancer patients was 12.51 +/- 3.39, while their mean FACIT-sp total score was 26.10 +/- 6.93 and their mean BRS total score was 16.1 +/- 7.05. It was found that FACIT-sp total score affected DAS and BRS total score positively, while DAS total score affected BRS total score negatively (p < .001). It was found that cancer patients had moderate level of spiritual well-being and psychological resilience and high level of death anxiety. It was also found that death anxiety and psychological resilience of cancer patients increased as their spiritual well-being levels increased. Psychological resilience was found to decrease as death anxiety increased.
Keywords: cancer; death anxiety; patient; psychological resilience; spiritual well-being